Preterm premature rupture of membranes: prediction of risks in women of Zaporizhzhia region of Ukraine - Lyubomirskaya, K.; Krut, Yu. Ya.; Sergeyeva, L.; Khmil, S.; Lototska, O.; Petrenko, N.; Kamyshnyi, A.; Любомирська, Катерина Сергіївна; Круть, Юрій Якович; Сергєєва, Людмила Нільсівна; Хміль, С.; Лотоцька, О.; et al. (My University, 2020)
The etiology of preterm premature rupture of membranes (PPROM), which is responsible for approximately 30% cases of preterm birth (PTB) is not yet fully understood. Aim: The aim of the study was to create a mathematical model for prognostication of PPROM based on the anamnesis, clinical data, laboratory findings and genetics predictors. Materials and methods: The study involved 80 women with PPROM (between 26 and 34 weeks of gestation) and 50 women having term birth (>37 weeks of gestation) of Zaporizhzhia region of Ukraine. Anamnesis, clinical, laboratory data and single nucleotide polymorphism sequencing of interleukin1 β (IL1β), tumor necrosis factor α(TNFα), interleukin4 (IL4), interleukin10 (IL10) and Relaxin 2 (RLN2) genes has been analyzed. Receiver operating characteristic analysis and multivariate logistic regression were used to PPROM predictors identification. Results: We have identified prognostic anamnestic (history of preterm birth), clinical (cervical insuffiency, compromised uteroplacental and fetal circulation), microbiological (vaginal dysbiosis) and hematological criteria for intra-amniotic contamination and further development of PPROM and PTB: WBC>12.3×109/L, GRAN>76%, LYM<19%, neutrophil lymphocyte ratio>3.87, Kalph-Kaliph leukocyte index of intoxication (LII) >3.4, Ostrovsky LII >2.8. Also we have found that GG genotype of IL10 gene polymorphism (rs1800872) leads to a 12.5-fold and CT genotype of RLN2 gene polymorphism (rs4742076) leads to a 17.0-fold increase in risk for PPROM. Conclusions: The prognostic model that we have suggested is an adequate and convenient instrument for practical medical use, which allows for assessment of PPROM probability with a 85% sensitivity and a 72% specificity.
Keywords: preterm premature rupture of membranes; risks prediction